The Study of Coexistance of Superconductivity and Spin Glass in Fe Pnictide(Fe1+YSeXTe1−X) - Anteneh, Yesigat; Psingh, (Journal of Advances in Nanotechnology, 2020)
Superconductivity and magnetism were previously thought as incompatible until the discovery of some rare earth ternary compounds that shows the coexistence of superconductivity and magnetism. In some of the recently discovered iron based layered superconductors superconductivity and diamagnetic order system are coexist. That occurs in only 11 and 122 family. The present works we examine the possibility of coexistence of superconductivity and disorder of magnetic spin is called spin glass when freeze the system that can show the superconductivity and spin glass coexist. In this present work we can examine the possibility of coexistence of superconductivity and spin glass in detailed 11 family of Fe1+ySexTe1−x compound. We show that spin glass like behavior is present in FST for x = 0.1 - 0.15 we present evidence form magnetization measurement and characterized the short-range order with neutron scattering. One of our main results is that the short-range order is structural as well as magnetic order. The factor of magnetic order exchange in long range depend on temperature, pressure, number of doping and other external factor discussed it. We found mathematical expression for superconductor transition TC, spin glass temperature TgSusceptibility x(q), and retardation time τ using for born approximation and digamma function depend on wave vector(q) and cut off frequency(ω) in the region coexistence of superconductivity and spin glass in Fe1+ySexTe1−xcompound. Aim: To improve the coexistence of superconductivity and spin glass and to examine the associated Factor of electron doping and temperature in experimental and theoretical aspect of their coexistence.
Keywords: coexistence; Superconductivity; spin glass; doping; susceptibility; ferromagnetism; Antiferromagnetism; pnictides.